2020
DOI: 10.3386/w26637
|View full text |Cite
|
Sign up to set email alerts
|

The Decline of Secured Debt

Abstract: The share of secured debt issued (as a fraction of total corporate debt) declined steadily in the United States over the twentieth century. This stems partly from financial development giving creditors greater confidence that high quality borrowers will respect their claims even if creditors do not obtain security up front. Consequently, such borrowers prefer retaining financial flexibility by not giving security up front. Instead, security is given contingently -when a firm approaches distress. This also expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 67 publications
(88 reference statements)
3
17
0
Order By: Relevance
“…Our analyses can also shed new light on the nature of secured debt, which is a classic issue in economics research (Berger and Udell, 1990;Donaldson, Gromb, and Piacentino, 2020;Benmelech, Kumar, and Rajan, 2020a;Rampini and Viswanathan, 2020). Although the academic literature typically associates secured debt with debt against separable or tangible assets (i.e., asset-based debt in our categorization), this is not necessarily the case in practice.…”
Section: Essence Of Secured Debtmentioning
confidence: 94%
See 2 more Smart Citations
“…Our analyses can also shed new light on the nature of secured debt, which is a classic issue in economics research (Berger and Udell, 1990;Donaldson, Gromb, and Piacentino, 2020;Benmelech, Kumar, and Rajan, 2020a;Rampini and Viswanathan, 2020). Although the academic literature typically associates secured debt with debt against separable or tangible assets (i.e., asset-based debt in our categorization), this is not necessarily the case in practice.…”
Section: Essence Of Secured Debtmentioning
confidence: 94%
“…Second, our work connects to research on debt structure, which has covered a number of issues, including loans versus bonds (Denis and Mihov, 2003;Uhlig, 2011, 2015;Crouzet, 2018), interactions among creditors (Bolton and Scharfstein, 1996;Repullo and Suarez, 1998;Park, 2000), secured debt (Donaldson, Gromb, and Piacentino, 2020;Benmelech, Kumar, and Rajan, 2020a), interest rates (Luck and Santos, 2020;Benmelech, Kumar, and Rajan, 2020b), and implications of asset-based and cash flow-based debt (Lian and Ma, 2020;Ivashina, Laeven, and Moral-Benito, 2020). In addition, some early work studies how liquidation costs affect debt choices of firms emerging from bankruptcy (Alderson and Betker, 1995).…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Kiyotaki and Moore 1997;Chaney, Sraer and Thesmar 2012;Adelino, Schoar and Severino 2015;Campello and Larrain 2016). Several papers have also shown that lenders become more willing to lend collateralised during downturns (Lian and Ma forthcoming;Liberti and Sturgess 2014;Benmelech et al 2020aBenmelech et al , 2020bDe Jonghe et al 2020). However, it is difficult to analyse the effect of collateralisation on borrowers' access to credit, because available data typically do not permit controlling for endogenous factors.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Empirically, an important dimension along which cov-lite loans often but not always differ from bonds is that most bonds are unsecured (see Benmelech, Kumar, and Rajan (2020) for the decline of use of collateral in bonds) and cov-lite loans are almost always secured. For borrowers, putting up collateral against borrowing is costly as it reduces financial flexibility (see Benmelech, Kumar, and Rajan (2020) to a given size. When banks are limited in how much of a loan they can hold, they can sell parts of the loan to non-bank investors.…”
Section: 4a the Legal Status Hypothesismentioning
confidence: 99%